Biotransformation Of Cis/Trans 3,7-Dimethyl-2,6-Octadien-1-Ol Mediated By Saccharomyces Cerevisiae - Khor, Guat Kheng (2011)
Biotransformation of geraniol and nerol mediated by Saccharomyces cerevisiae was performed. Linalool and geraniol were mainly obtained from nerol using growing cells but only isomerisation to geraniol occurred using resting cells. Reductive biotransfomation of geraniol to citronellol was apparently more effective with resting cells system. Combination of full factorial design with response surface methodology (RSM) was applied in order to evaluate the effects of cell density, substrate concentration and biotransformation time on product concentrations. The productivity increased proportionally with cell density. However, inhibition was observed at higher substrate concentrations.